Spatial Analysis of Elderly Access to Photographic Services and Their Rating in Skopje - Gjorgjioski, Filip; Naumoski, Andreja (IEEE, 2022)
Capturing the moments in everyone's life are a way of looking and reminiscing of the past, but also a gaze into the future. This is especially true when we talk in the context of our older generations, the elderly people, who are not technology savvy, and they need help regarding digital devices and technologies. It is well known that the elderly population have developed a strong habit of obtaining hard-copy memories when it comes to the subject of photography. So, in this paperwork, we focus on the elderly population and the spatial access to the photography services, since many of them don't have younger family members or relatives to assist them. We start our analysis with the interpolation of the user satisfactory rating of the photographic studios, as we proceed with population clustering and the relationship between the elderly population and the locations of the photographic studios. Later we advance our spatial analysis of the photographic shops with multiple ring buffers to identify places of near proximity to highest population density. According to the models, most of the central area of the city is well covered with photographic services., and we also pinpoint possible places where photographic business could be opened to increase services and customer satisfaction. In future we plan to investigate the influence of other related services and stores, in relationship with nearby population density.